Pediatric patients accessing Accident and Emergency Department (A&E) for non-urgent treatment: Why do parents take their children to the A&E?. (September 2021) - Biagioli, Valentina; Pol, Alessandra; Gawronski, Orsola; Carlin, Claudia; Cirulli, Luisa; Piga, Simone; Stelitano, Rocco; Offidani, Caterina; Raucci, Umberto; Reale, Antonino; Tiozzo, Emanuela; Villani, Alberto; et al.
Highlights: The most common symptoms for accessing the A&E were fever, rash, and cough. Skin rash was the most frequent single symptom for taking a child to the A&E. Few parents reported being good at managing breathing difficulties and skin rashes. Parents believed their child required immediate treatment and rapid tests. Parents thought they could quickly resolve their child's problem at the A&E. Abstract: Introduction: About 20–30% of children access the Pediatric Accident and Emergency Department (A&E) for non-urgent health care that should normally follow other health care paths. This study aimed to investigate why parents take their children to the A&E for non-urgent visits rather than using primary care services. Methods: A one-year cross-sectional study was conducted in a large pediatric A&E in Italy. A paper-and-pencil 40-item questionnaire was administered to parents of children aged between 3 months to 6 years who accessed the A&E for non-urgent visits between July 2018 and June 2019. Results: Parents of 238 children completed the questionnaire (mean age = 2.6 years; male 58%). The most common symptoms were fever (n = 105; 44.1%) and skin rash (n = 63; 26.5%); symptoms usually started more than 24 h earlier (n = 163; 69.4%). Reasons for accessing the A&E for non-urgent visits included the availability of rapid medical tests (n = 71; 29.8%), deterioration of the clinical conditions after the pediatrician's visit (n = 67; 28.2%), and the perceived need for urgent care (n = 65; 27.3%). Besides, 26.6% (n = 63) of parents reported not being able to contact their pediatrician before accessing A&E. Conclusion: Parents may need further education to distinguish between urgent and non-urgent pediatric health conditions.